The Psychological Inflexibility in Pain Scale (PIPS) in Brazilian patients with chronic cancer pain: translation, cross-cultural adaptation, and validation study - Aguiar, Sergio Paulo Mariano de; Bassi-Dibai, Daniela; Mendes, Letícia Padilha; Cutrim, Naara Rayane Moura; Guedes, César Leonardo Ribeiro; Pinheiro, Jocassia Silva; Morais, Daniel Nunes; Campos Neto, Carlos Wagner de Sousa; Leal, Plínio da Cunha; Dibai Filho, Almir Vieira (São Paulo Medical Journal, 2026)
BACKGROUND: The Psychological Inflexibility in Pain Scale (PIPS) was developed to measure avoidance and cognitive fusion. OBJECTIVES: To translate, cross-culturally adapt, and analyze the measurement properties of the Psychological Inflexibility in Pain Scale (PIPS) in Brazilian patients with chronic cancer pain. METHODS: Questionnaire translation, cross-cultural adaptation, and validation studies were conducted in two hospitals in northeastern Brazil. The measurement properties tested included structural validity, construct validity, reliability, and internal consistency. The following assessment instruments were used in addition to the PIPS: Pain Catastrophizing Scale (PCS), Barthel Index, Edmonton Symptom Assessment Scale (ESAS), and Hospital Anxiety and Depression Scale (HADS). RESULTS: The study sample consisted of 122 patients, most of whom were women (65.6%) with a mean age of 49 years. Most patients had uterine cancer (23%) and leukemia (9.8%). We identified problems in the two-dimensional structure of the PIPS by presenting three inadequate fit indices. Adequate reliability was observed in both domains. Regarding the avoidance domain, there was a correlation with a magnitude > 0.30 with the depression domain of the HADS, and correlations with a magnitude < 0.30 with the anxiety domain of the HADS, the PCS domains, and the Barthel Index. The cognitive fusion domain did not correlate with any of these scales (P > 0.05). No ceiling or floor effects were observed. CONCLUSION: The Brazilian version of the PIPS is reliable; however, the instrument does not have a valid internal structure and the cognitive fusion domain is not a valid construct.